Repeated cross‐sectional study of Trypanosoma cruzi in shelter dogs in Texas, in the context of Dirofilaria immitis and tick‐borne pathogen prevalence - Carolyn L. Hodo; Jessica Y. Rodriguez; Rachel Curtis‐Robles; Italo B. Zecca; Karen F. Snowden; Kevin J. Cummings; Sarah A. Hamer (Journal of Veterinary Internal Medicine, 2019)
Background Vector‐borne diseases have an adverse impact on health of dogs, and infected dogs can be sentinels for human infection. Infection with Trypanosoma cruzi, an agent of Chagas disease, causes fatal heart disease in dogs across the southern United States but has been neglected from wide‐scale prevalence studies. Objectives To determine the prevalence of exposure to T. cruzi, Ehrlichia spp., Anaplasma spp., Borrelia burgdorferi, and infection with Dirofilaria immitis among dogs in shelters across Texas and to identify risk factors for T. cruzi seropositivity. Animals Six hundred and eight dogs. Methods This repeated cross‐sectional study was performed by collecting blood from ~30 dogs during each of the 3 visits to 7 shelters. We tested serum for antibodies to T. cruzi using 2 tests in series and for antibodies to Ehrlichia spp., Anaplasma spp., and B. burgdorferi and D. immitis antigen using the IDEXX SNAP 4DX Plus point‐of‐care test. DNA was extracted from blood clots and tested for T. cruzi DNA and strain type via quantitative polymerase chain reactions (qPCR). We used logistic regression to assess risk factors. Results One hundred ten (18.1%) of 608 dogs were seropositive for T. cruzi. Prevalence of exposure to the other vector‐borne agents was: Ehrlichia spp. 3.6%; Anaplasma spp. 6.9%; B. burgdorferi 0.2%; and D. immitis infection 16.0%. Six of 559 (1.1%) dogs were qPCR‐positive for T. cruzi. Conclusions and Clinical Importance T. cruzi seroprevalence was comparable to D. immitis prevalence and higher than seroprevalence of the tick‐borne pathogens. T. cruzi is an underrecognized health threat to dogs across Texas and possibly other southern states where triatomine vectors are endemic.